Identification of novel cytokine biomarkers of hexanal exposure associated with pulmonary toxicity. (October 2017) - Cho, Yoon; Song, Mi-Kyung; Kim, Tae Sung; Ryu, Jae-Chun
Abstract: We aimed to investigate whether exposure to low-molecular-weight saturated aliphatic aldehydes induces an airway inflammation related to lung toxicity. In previous studies, we identified that several aldehydes induced inflammatory responses through the secretion of pro-inflammatory cytokines. Here, we elucidate on whether hexanal exposure induces the lung inflammatory response through the secretion of cytokines. Hexanal is one of the aldehydes, which are major components of indoor environmental irritants. Based on a multiplexed cytokine antibody array, we investigated the cytokine expression profiles to identify the significant biomarkers of hexanal exposure and to predict the possibility of adverse effects on pulmonary toxicity using in vitro and in vivo model systems. We identified the cytokines as biomarkers involved in LEPTIN, Interleukin(IL)-10, MCP-1, and VEGF that showed similar expression patterns in both in vitro and in vivo models under hexanal exposure. These cytokines are known to be associated with diverse lung diseases, such as lung fibrosis, chronic obstructive pulmonary disease (COPD), and non-small cell lung cancer. Although further studies are needed to identify the mechanisms that underlie hexanal pulmonary toxicity, these results provide the key cytokine biomarkers in response to hexanal exposure and indicate meaningful mechanistic previewing that can be indirectly attributed to lung disease. Graphical abstract: Highlights: Cytokine is important novel biomarkers in risk assessment. The cytokines LEPTIN, IL-10, MCP-1 and VEGF are important novel biomarker in hexanal exposure risk assessment. Hexanal is a well-known eye irritant and may cause respiratory irritation. It indicates the meaningful mechanistic previewing of hexanal-inflammatory lung disease.